2017
DOI: 10.1016/j.apenergy.2017.08.013
|View full text |Cite
|
Sign up to set email alerts
|

Online short-term forecast of greenhouse heat load using a weather forecast service

Abstract:  Users may download and print one copy of any publication from the public portal for the purpose of private study or research.  You may not further distribute the material or use it for any profit-making activity or commercial gain  You may freely distribute the URL identifying the publication in the public portal If you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Indoor and outdoor temperatures, outdoor water vapor density, soil temperature, and outdoor wind speed are assumed to be constant during the regulation time period. Based on ( 17)-( 20), the switching time of the HL from xin1 to xin2 can be calculated using (35)…”
Section: ) Regulation Potential Model Of Hlmentioning
confidence: 99%
“…Indoor and outdoor temperatures, outdoor water vapor density, soil temperature, and outdoor wind speed are assumed to be constant during the regulation time period. Based on ( 17)-( 20), the switching time of the HL from xin1 to xin2 can be calculated using (35)…”
Section: ) Regulation Potential Model Of Hlmentioning
confidence: 99%
“…[29] gives a method to circumvent the problem faced by the ordinary least squares estimator in the presence of co-linear features. The model used here is the same as that given in (5), but in addition to the regular assumption on ε, the model also considers a prior Gaussian distribution p(q) on the parameters q and maximizes the logarithm of the likelihood L ðqÞ ¼ pðqjyÞ using Bayes rules, i.e.,:…”
Section: Ridge Regressormentioning
confidence: 99%
“…Here, with the same case study as that of [2], the best error was shown to be 11.5%, albeit for an extended test period including the autumn months. In more recent work [5], a customized recursive least square forecaster was used for forecasting the short term greenhouse heat load in a district heating system; the model was shown to be a simple, yet reliable forecaster. Polynomial regression models were shown to supplement artificial neural networks in Ref.…”
Section: Introductionmentioning
confidence: 99%
“…There is also research relating to the role of errors within the weather forecast on the uncertainty in the prediction of greenhouse heating demand (Sigrimis et al, 2001;Vogler-Finck et al, 2017). While other studies have assessed the impact of forecast error on the performance of greenhouses that are controlled using an optimal controller (Doeswijk et al, 2006;Tap et al, 1996).…”
Section: Uncertainty Analysis In Greenhouse Horticultural Researchmentioning
confidence: 99%
“…The potential impact of weather forecast errors on greenhouse prediction uncertainty has been partially addressed. Vogler-Finck et al, (2017) use a simple linear model and a recursive least squares approach to predict the heat demand of a Danish greenhouses using short term weather forecasts. Vogler-Finck concluded that the inclusion of real weather forecasts significantly improved the online prediction of heat load over using simplified weather forecasts.…”
Section: Introductionmentioning
confidence: 99%